Untargeted plasma metabolomics identifies broad metabolic perturbations in glycogen storage disease type I. Issue 2 (10th November 2021) - Mathis, Tamara; Poms, Martin; Köfeler, Harald; Gautschi, Matthias; Plecko, Barbara; Baumgartner, Matthias R.; Hochuli, Michel
Abstract: Background: The metabolic defect in glycogen storage disease type I (GSDI) results in fasting hypoglycemia and typical secondary metabolic abnormalities (eg, hypertriglyceridemia, hyperlactatemia, hyperuricemia). The aim of this study was to assess further perturbations of the metabolic network in GSDI patients under ongoing treatment. Methods: In this prospective observational study, plasma samples of 14 adult patients (11 GSDIa, 3 GSDIb. Mean age 26.4 years, range 16‐46 years) on standard treatment were compared to a cohort of 31 healthy controls utilizing ultra‐high performance liquid chromatography (UHPLC) in combination with high resolution tandem mass spectrometry (HR‐MS/MS) and subsequent statistical multivariate analysis. In addition, plasma fatty acid profiling was performed by GC/EI‐MS. Results: The metabolomic profile showed alterations of metabolites in different areas of the metabolic network in both GSD subtypes, including pathways of fuel metabolism and energy generation, lipids and fatty acids, amino acid and methyl‐group metabolism, the urea cycle, and purine/pyrimidine metabolism. These alterations were present despite adequate dietary treatment, did not correlate with plasma triglycerides or lactate, both parameters typically used to assess the quality of metabolic control in clinical practice, and were not related to the presence or absence of complications (ie, nephropathy or liver adenomas). Conclusion: The metabolic defect of GSDI has profound effects on a variety of metabolic pathways in addition to the known typical abnormalities. These alterations are present despite optimized dietary treatment, which may contribute to the risk of developing long‐term complications, an inherent problem of GSDI which appears to be only partly modified by current therapy.